The role of Perpustakaan Alam Malabar in supporting community empowerment - Zarra Zakiyyah Izzaturrahmah Gunadi; Rully Khairul Anwar; Ute Lies Siti Khadijah (Perpustakaan Universitas Gadjah Mada, 2025)
Introduction. As an information institution, the library significantly contributes to improving the community's ability. This role can be implemented by effectively utilizing information resources and library programs. This study aims to describe the role of Perpustakaan Alam Malabar in supporting community empowerment through information sources and programs that focus on literacy and environmental sustainability. Research Methods. This research applies descriptive qualitative methods with case study and data collection techniques through observation, interviews, and literature review. Data Analysis. Data analysis is carried out in stages: data reduction, presentation, and conclusion. Results. Perpustakaan Alam Malabar supports community empowerment through access to information and programs that improve education and environmental awareness. Following Jim Ife's Theory, this library emphasizes the importance of education and awareness in shaping an empowered community. This library's information resources and programs can improve the community's knowledge, skills, and environmental awareness. Conclusion. Perpustakaan Alam Malabar, with its green library concept, has played an essential role in supporting community empowerment as a provider of information sources, both books and social media content, and organizing programs about environmental sustainability.